2021
DOI: 10.1111/1462-2920.15823
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of a vampire: ‘Candidatus Absconditicoccus praedator’

Abstract: Halorhodospira halophila, one of the most-xerophilic halophiles, inhabits biophysically stressful and energetically expensive, salt-saturated alkaline brines. Here, we report an additional stress factor that is biotic: a diminutive Candidate-Phyla-Radiation bacterium, that we named 'Ca. Absconditicoccus praedator' M39-6, which predates H. halophila M39-5, an obligately photosynthetic, anaerobic purple-sulfur bacterium. We cultivated this association (isolated from the hypersaline alkaline Lake Hotontyn Nur, Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 105 publications
6
56
0
Order By: Relevance
“…One major lineage of the domain Bacteria, Patescibacteria (also known as Candidate Phyla Radiation/CPR) [1,2], is a highly diverse group of bacteria, widely inhabiting [3,4] natural and artificial ecosystems [5,6], characterized with small cell/genome size [7] and poor (genomically predicted) abilities to synthesize cellular building blocks [4] suggestive of symbiotic dependency for cell growth. Most members remain uncultured, leaving major knowledge gaps in the range and nature of their symbioses, but several cultivation-based studies have demonstrated host-specific symbiotic/parasitic interactions between Patescibacteria and other bacteria [8][9][10][11]. This pointed towards specialization towards bacteria-bacteria symbioses, especially given parallels with DPANN, an archaeal analog who has only been observed to interact with other archaea [4,12]; however, one study has reported Patescibacteria-eukarya symbiosis [13], indicating that the Patescibacteria host range reaches beyond bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…One major lineage of the domain Bacteria, Patescibacteria (also known as Candidate Phyla Radiation/CPR) [1,2], is a highly diverse group of bacteria, widely inhabiting [3,4] natural and artificial ecosystems [5,6], characterized with small cell/genome size [7] and poor (genomically predicted) abilities to synthesize cellular building blocks [4] suggestive of symbiotic dependency for cell growth. Most members remain uncultured, leaving major knowledge gaps in the range and nature of their symbioses, but several cultivation-based studies have demonstrated host-specific symbiotic/parasitic interactions between Patescibacteria and other bacteria [8][9][10][11]. This pointed towards specialization towards bacteria-bacteria symbioses, especially given parallels with DPANN, an archaeal analog who has only been observed to interact with other archaea [4,12]; however, one study has reported Patescibacteria-eukarya symbiosis [13], indicating that the Patescibacteria host range reaches beyond bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies [30, 34], many of the recovered Patescibacteria MAGs had very small genomes (often ∼1MB or smaller; Table S2) with highly reduced metabolic potential, often lacking detectable genes for synthesis of fatty acids, nucleotides, and most amino acids (Table S6). Gene patterns also suggested that many of the organisms are obligate anaerobes, lacking aerobic respiration, and that they likely form symbiotic or parasitic associations with other microbes, as has been shown for Patescibacteria cultivated thus far from the Absconditabacterales and Saccharibacteria [39, 40, 47, 48].…”
Section: Resultsmentioning
confidence: 89%
“…To date, only a few of its members ( i.e. , phyla Saccharimonadia and Gracilibacteria ) have been cultured ( Soro et al , 2014 ; He et al , 2015 ; Ibrahim et al , 2021 ; Yakimov et al , 2021 ). These bacteria are parasitic on other bacteria for sustenance; however, since most of them cannot be cultured, the mechanisms underlying their existence are unclear.…”
mentioning
confidence: 99%
“…Patescibacteria are commonly characterized by a small genome size (approximately 1.0‍ ‍Mbp) ( Lemos et al , 2020 ; Nakai, 2020 ), limited metabolic potential, and fermentation-based metabolism ( Wrighton et al , 2012 , 2014 ; Albertsen et al , 2013 ; Lemos et al , 2020 ). However, the physiology and phylogeny of Patescibacteria have not yet been elucidated in detail, except for some cultures in the phyla Saccharimonadia and Gracilibacteria ( Soro et al , 2014 ; He et al , 2015 ; Moreira et al , 2021 ; Yakimov et al , 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation